1998
DOI: 10.1083/jcb.141.2.309
|View full text |Cite
|
Sign up to set email alerts
|

Centromere Protein B Null Mice are Mitotically and Meiotically Normal but Have Lower Body and Testis Weights

Abstract: CENP-B is a constitutive centromere DNA-binding protein that is conserved in a number of mammalian species and in yeast. Despite this conservation, earlier cytological and indirect experimental studies have provided conflicting evidence concerning the role of this protein in mitosis. The requirement of this protein in meiosis has also not previously been described. To resolve these uncertainties, we used targeted disruption of the Cenpb gene in mouse to study the functional significance of this protein in mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
149
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 224 publications
(158 citation statements)
references
References 74 publications
(126 reference statements)
8
149
0
1
Order By: Relevance
“…This finding is not surprising as it was reported that an impact on fertility should have an estimated sperm count reduction to 10% or less (22). Furthermore, previous reports have demonstrated several animal models with reduced sperm count but normal fertility (22)(23)(24)(25)(26). ADP-ribosylation factor-like 4 (Arl4) is a GTP-binding protein that shuttles between the nucleus and intracellular organelles depending on GTP͞GDP-binding status.…”
Section: Altered Expression Of Sertoli Cells' Functional Genes Junctmentioning
confidence: 91%
See 1 more Smart Citation
“…This finding is not surprising as it was reported that an impact on fertility should have an estimated sperm count reduction to 10% or less (22). Furthermore, previous reports have demonstrated several animal models with reduced sperm count but normal fertility (22)(23)(24)(25)(26). ADP-ribosylation factor-like 4 (Arl4) is a GTP-binding protein that shuttles between the nucleus and intracellular organelles depending on GTP͞GDP-binding status.…”
Section: Altered Expression Of Sertoli Cells' Functional Genes Junctmentioning
confidence: 91%
“…In addition, FSH␀ has been reported to play a role in spermatogenesis and mice lacking FSH␀ are also fertile despite having a reduced testis size and epididymal sperm count (25,26). Furthermore, centromere protein B is a DNA-binding protein required for meiosis, and its deletion caused a reduction in testis weight by 30% and a 40% reduction in sperm count without a reduction in fertility (24). Finally, mice with disrupted protein inhibitor of activated STAT splice variant also show a similar phenotype with absolute testicular weight decrease of 23% and sperm count decrease of 19% (22).…”
Section: Altered Expression Of Sertoli Cells' Functional Genes Junctmentioning
confidence: 99%
“…CENP-E, CENP-F, INCENP, survivin, MCAK, ZWINT-1, ZW10, MAD-1, MAD-2, BUB1, BUBR1, and BUB3) associate with the centromere during specific stages of the cell cycle. Constitutive proteins CENP-A, CENP-C, and CENP-H are essential for correct kinetochore assembly and function as evidenced by a lethal phenotype in gene knockout and antibody/RNA inhibition studies in mouse, worm, and chicken DT40 cells (13)(14)(15)(16)(17)(18)(19)(20)(21), whereas CENP-B appears to be functionally redundant for centromere activity (22)(23)(24). Numerous gene knockout and inhibition studies have demonstrated that many of the transient proteins have essential roles in normal mitotic functions, such as INCENP, survivin, CENP-E, BUB3, and MAD2 (25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…For the preparation of nuclear protein extracts, 10 7 cells were harvested and lysed in ice-cold lysis buffer as previously described (24).…”
mentioning
confidence: 99%
“…Human centromeric DNA contains the 17-bp "CENP-B box," which directly recruits the centromere protein CENP-B (Masumoto et al 1989). CENP-B knockout mice are for the most part phenotypically normal (Hudson et al 1998;Kapoor et al 1998;Perez-Castro et al 1998) and functional neocentromeres lack CENP-B (Saffery et al 2000). Moreover, CENP-B is absent from the human Y chromosome (Earnshaw et al 1987) and no CENP-B functional homologs have been identified in Xenopus, zebrafish, C. elegans, or Drosophila to date.…”
Section: Histone Modificationsmentioning
confidence: 99%